HNF1B deletions in patients with young‐onset diabetes but no known renal disease. Issue 1 (13th December 2012) - Edghill, E. L.; Stals, K.; Oram, R. A.; Shepherd, M. H.; Hattersley, A. T.; Ellard, S.
<x xml:space="preserve">Abstract</x> Diabet. Med. 30, 114–117 (2013) Abstract Aims Hepatocyte nuclear factor 1β (HNF1B) mutations cause a syndrome of renal cysts and diabetes, with whole gene deletions accounting for approximately 50% of cases. The severity of the renal phenotype is variable, from enlarged cystic kidneys incompatible with life to normal renal development and function. We investigated the prevalence of HNF1B deletions in patients with diabetes but no known renal disease. Methods We tested 461 patients with familial diabetes diagnosed before 45 years, including 258 probands who met clinical criteria for maturity‐onset diabetes of the young (two generations affected and at least one family member diagnosed under 25 years). A fluorescent polymerase chain reaction assay was used to analyse two intragenic polymorphic HNF1B markers and identify heterozygous patients who therefore did not have whole gene deletions. Those patients homozygous for both markers were then tested for an HNF1B deletion using multiplex ligation‐dependent probe amplification. Results Heterozygous HNF1B intragenic polymorphisms were identified in 337/461 subjects. Multiplex ligation‐dependent probe amplification analysis showed an HNF1B gene deletion in three of the remaining 124 probands, all of whom met the criteria for maturity‐onset diabetes of the young. Testing of their relatives identified three additional deletion carriers and ultrasound scanning showed renal developmental abnormalities in three of these six patients. Conclusions We estimate that HNF1B mutations account for < 1% of cases of maturity‐onset diabetes of the young. Although HNF1B mutations are a rare cause of diabetes in the absence of known renal disease, a genetic diagnosis of renal cysts and diabetes syndrome is important as it raises the possibility of subclinical renal disease and the 50% risk of renal cysts and diabetes syndrome in the patient's offspring.